Small‐field measurement and Monte Carlo model validation of a novel image‐guided radiotherapy system. Issue 11 (22nd October 2021) - Shi, Mengying; Chuang, Cynthia F.; Kovalchuk, Nataliya; Bush, Karl; Zaks, Daniel; Xing, Lei; Surucu, Murat; Han, Bin
Abstract: Purpose: The RefleXion™ X1 is a novel radiotherapy system that is designed for image‐guided radiotherapy, and eventually, biology‐guided radiotherapy (BgRT). BgRT is a treatment paradigm that tracks tumor motion using real‐time positron emission signals. This study reports the small‐field measurement results and the validation of a Monte Carlo (MC) model of the first clinical RefleXion unit. Methods: The RefleXion linear accelerator (linac) produces a 6 MV flattening filter free (FFF) photon beam and consists of a binary multileaf collimator (MLC) system with 64 leaves and two pairs of y ‐jaws. The maximum clinical field size achievable is 400 × 20 mm 2 . The y ‐jaws provide either a 10 or 20 mm opening at source‐to‐axis distance (SAD) of 850 mm. The width of each MLC leaf at SAD is 6.25 mm. Percentage depth doses (PDDs) and relative beam profiles were acquired using an Edge diode detector in a water tank for field sizes from 12.5 × 10 to 100 × 20 mm 2 . Beam profiles were also measured using films. Output factors of fields ranging from 6.25 × 10 to 100 × 20 mm 2 were measured using W2 scintillator detector, Edge detector, and films. Output correction factors k of the Edge detector for RefleXion were calculated. An MC model of the linac including pre‐MLC beam sources and detailed structures of MLC and lower y ‐jaws was validated against the measurements. Simulation codes BEAMnrc and GATE were utilized. Results: The diode measured PDD at 10 cm depth (PDD10) increases from 53.6% to 56.9% as the field opens from 12.5 × 10 to 100 × 20 mm 2 . The W2‐measured output factor increases from 0.706 to 1 as the field opens from 6.25 × 10 to 100 × 20 mm 2 (reference field size). The output factors acquired by diode and film differ from the W2 results by 1.65% (std = 1.49%) and 2.09% (std = 1.41%) on average, respectively. The profile penumbra and full‐width half‐maximum (FWHM) measured by diode agree well with the film results with a deviation of 0.60 mm and 0.73% on average, respectively. The averaged beam profile consistency calculated between the diode‐ and film‐measured profiles among different depths is within 1.72%. By taking the W2 measurements as the ground truth, the output correction factors k for Edge detector ranging from 0.958 to 1 were reported. For the MC model validation, the simulated PDD10 agreed within 0.6% to the diode measurement. The MC‐simulated output factor differed from the W2 results by 2.3% on average (std = 3.7%), while the MC simulated beam penumbra differed from the diode results by 0.67 mm on average (std = 0.42 mm). The MC FWHM agreed with the diode results to within 1.40% on average. The averaged beam profile consistency calculated between the diode and MC profiles among different depths is less than 1.29%. Conclusions: This study represents the first small‐field dosimetry of a clinical RefleXion system. A complete and accurate MC model of the RefleXion linac has been validated.